Olahan Pangan Sehat dari Ikan Gabus Giling dengan Ekstraksi Daun Kelor (Pempek Kelor) di Lorong Oxindo Kelurahan 1 Ulu Palembang - Sherly Desliyanah; Icuk M Sakir; Diah Putri Islamy; Julia Tessa; Aryani Ningsih; Rahmalia Afriyani (Universitas Maritim AMNI Semarang, 2024)
Snakehead fish or Ophiocephallus striatus provides many benefits to the human body. Especially for children, pregnant women, and diabetics. There are many preparations that can be made using Snakehead Fish, one of which is Pempek. Pempek which is a typical food from the city of Palembang, in addition to containing a lot of protein and carbohydrates. It turns out that it can be a healthier processed food by mixing moringa leaf extract in it. Moringa or Moringa eleifera in addition to having low calories, moringa leaves also contain iron, magnesium, phosphorus, calcium, potassium, and zinc. Because of the efficacy of moringa leaves, the WHO even dubbed it as the Miracle Tree. The purpose of this community service activity is to inform and provide assistance to the people of Village 1 Ulu Lorong Oxindo on how to make healthy food from ground snakehead fish with moringa leaf extract. In this service, using the counseling method by providing material on the introduction of moringa products and their nutritional value, as well as direct training in making moringa pempek. It is hoped that the results of the activities will help develop attractive and sustainable tourism products, encourage local economic growth, and showcase healthy culinary innovations as part of the Palembang tourism experience.